The Correlation Between Students' Knowledge Of Learning Styles And Success In Using Writing Strategies: A Study At Batna 2 University (El-Wahat Journal for Research and Studies, 2026)
This study investigates the correlation between students' awareness of their learning styles and their success in implementing appropriate writing strategies for paragraph composition. Conducted at Batna 2 University, the research involved 41 undergraduate students (18 males and 23 females) enrolled in an English writing course. Participants completed the VARK (Visual, Auditory, Read/Write, Kinesthetic) learning styles questionnaire and received targeted instruction on writing strategies aligned with different learning preferences. Pre- and post-intervention assessments measured students' ability to effectively apply learned strategies in paragraph writing tasks. Statistical analysis revealed a significant positive correlation (r = 0.743, p < 0.001) between learning style awareness and strategy implementation success. Students who demonstrated higher metacognitive awareness of their learning preferences showed substantially greater improvement in writing performance, with effect sizes ranging from moderate to large across different learning style categories. These findings suggest that explicit instruction in learning style identification enhances students' strategic approach to writing tasks and contributes to improved academic outcomes in composition courses.
Keywords: Learning styles, Writing strategies, VARK model, Metacognitive awareness, Academic writing, Paragraph composition, Strategy instruction